Peace operations - Diehl, Paul F. (Paul Francis); Balas, Alexandru (Malden Polity press, 2014)
Peacekeeping has gradually evolved to encompass a broad range of different conflict management missions and techniques, which are incorporated under the term 'peace operations'. Well over 100 missions have been deployed, the vast majority within the last twenty years. This book provides an overview of the central issues surrounding the development, operation and effectiveness of peace operations. Among many features, the book traces the historical development of peace operations from their origins in the early 20th century through the development of modern peace building missions, tracks changes over time in the size, mission and organization of peace operations, analyses different organizational, financial and troop provisions for peace operations, as well as assessing alternatives, lays out criteria for evaluating peace operations and details the conditions under which such operations are successful.
The Historical Evolution and Record of Peace Operations -- The Organization of Peace Operations -- The Success and Failure of Peace Operations -- Ten Challenges for Future Peace Operations.
Includes bibliographical references (pages 230-241) and index.
Keywords: Peace-building.; Peacekeeping forces; 89.76 polemology; Peace-building.; Peacekeeping forces; Friedensmission; Vredesoperaties; Politics and Government; Geschiedenis (vorm)